2006
DOI: 10.1001/archpsyc.63.4.426
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of a New Behavioral Treatment for Drug Abuse in People With Severe and Persistent Mental Illness

Abstract: The BTSAS program is an efficacious treatment. Further work needs to be done to increase the proportion of eligible patients who are able to become engaged in treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
192
0
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(210 citation statements)
references
References 49 publications
4
192
0
14
Order By: Relevance
“…34 MI has been shown to improve patients' general health status or well-being, promote physical activity, help develop healthier nutritional habits, and manage chronic conditions such as mental illness, hypertension, hypercholesterolemia, obesity, and diabetes. [37][38][39][40][41] Randomized controlled trials have shown that brief MI training for clinicians is effective for improving patient medication adherence, especially if there is follow-up contact after an initial training, 42,43 and even at low doses (i.e., two or three sessions). MI is effective as a pretreatment adjunct and as an approach for less motivated or prepared patients, and may be applied for a wide range of medications across diverse populations.…”
Section: Motivational Interviewing and Counselingmentioning
confidence: 99%
“…34 MI has been shown to improve patients' general health status or well-being, promote physical activity, help develop healthier nutritional habits, and manage chronic conditions such as mental illness, hypertension, hypercholesterolemia, obesity, and diabetes. [37][38][39][40][41] Randomized controlled trials have shown that brief MI training for clinicians is effective for improving patient medication adherence, especially if there is follow-up contact after an initial training, 42,43 and even at low doses (i.e., two or three sessions). MI is effective as a pretreatment adjunct and as an approach for less motivated or prepared patients, and may be applied for a wide range of medications across diverse populations.…”
Section: Motivational Interviewing and Counselingmentioning
confidence: 99%
“…For treatment compliance, the effect size was medium ( Three studied the effect of MI plus CBT on treatment engagement, all eight studied the effect of MI plus CBT on substance abuse, and one also studied the effect of MI plus CBT on HIV viral load (Parsons, Golub, Rosof, & Holder, 2007). The three studies that examined the effect of MI on engagement showed an increase in participation (Bellack, Bennett, Gearon, Brown, & Yang, 2006;Carroll et al, 2006;Parsons et al, 2007), and six of the eight found at least one positive effect for outcome (Baker et al, 2006;Baker et al, 2005;Bellack et al, 2006;Parsons et al, 2007;Stein, Herman, & Anderson, 2009), suggesting that MI complements other treatments by improving both engagement and outcome.…”
Section: As a Complement To Cbtmentioning
confidence: 99%
“…The significant reduction in cocaine use in the ATM condition is noteworthy because there is limited empirical support for any specific substance abuse treatment for indigent people with concomitant substance use and severe and persistent mental disorders (25). Some of the treatments that have shown promise are quite extensive-residential treatment (26), case management (27), a multi-component biweekly approach (24), and incentivized participation in a Veterans Health Administration work program (28).…”
Section: Discussionmentioning
confidence: 99%